Connected Librarians : Tap Social Media to Enhance Professional Development and Student Learning - Robertson, Nikki D. (Book collections on Project MUSE., 2017)
This book discusses the responsibility of librarians to model the proper use of social media for students, and offers practical ideas for effectively using social media in school libraries.